GISP increases neurotransmitter receptor stability by down-regulating ESCRT-mediated lysosomal degradation - Kantamneni, Sriharsha (2009)
GPCR interacting scaffold protein (GISP) is a multi-domain brain-specific scaffold protein that can regulate GABA(B) receptor complexes by both enhancing their surface expression and by inhibiting their lysosomal degradation. GISP retards degradation of GABA(B) receptors through its interaction with tumour susceptibility gene 101 (TSG101), a member of the endosomal sorting complex required for transport (ESCRT) lysosomal sorting machinery. We show that in addition to GABA(B), GISP exerts a more general role to increase the steady-state levels of several neurotransmitter receptors. Further, GISP delays TSG101-dependent agonist-induced EGFR down-regulation in human embryonic kidney (HEK) 293 cells whereas a mutant GISP lacking the TSG101 binding domain has no effect. These data suggest that GISP acts as a negative regulator of TSG101-dependent lysosomal degradation and plays an important role in determining the availability of neurotransmitter receptors.